Correlation of Risk of Malignancy Index to Malignant Nature of Ovarian Tumours - Uzma Shahzad, Khurram Shahzad, Uzma Manzoor, Humaira Zafar, Sadaqat Ali, Abdul Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ovarian tumours are relatively common and account for 6% of female malignancies. Risk of malignancy index is used to categorize patients into high, intermediate and low risk groups. Aims: To categorize patients into groups according to risk of malignancy in preoperative periods and correlate the risk of malignancy and to histopathologic nature of ovarian tumours. Study design: Descriptive study. Place and duration of study: Department of Obstetrics & Gynaecology, Independent University Hospital, Faisalabad from 1st September 2017 to 31st August, 2018. Methodology: Sixty patients with adenexal masses were enrolled. All patients were investigated by tumour markers and imaging techniques to diagnose ovarian mass and then categorized according to risk of malignancy index. Staging laparotomy was done and specimen was sent for histopathology which was then correlated to risk of malignancy index. Results: There were 33 (55%) benign and 27 (45%) malignant cases. There were more pre-menopausal patients (43/60) 71.6% while (17/60) 28.33% were post-menopausal. Forty patients (66.6%) had complex ovarian masses (multi-locular, solid areas or associated with ascites). Twenty five (41.6%) patients fall in low risk group with RMI <25, in intermediate risk group with RMI 25-200 were 23 patients (38.3%) and high risk group with RMI >200 had 12 cases (20%). Conclusion: The study correlated the risk of malignancy to malignant nature of tumours. Key words: Risk of malignancy index (RMI), CA-125, Ovarian tumour